Effect of geometric configurations and curvature angle of corrugated sandwich structures on impact behavior - Bozkurt, Ilyas (Wiley, 2024)
The aim of this study is to numerically investigate the low-velocity impact behavior of carbon fiber reinforced orthogonal woven fabric composite sandwich structures with five different geometric configurations and four different curve angles. Low velocity impact simulations were performed in LS DYNA finite element program to investigate the effects of core configuration and curve angle on peak contact force, energy absorption efficiency and damage mode. A progressive damage analysis based on the combination of the Hashin damage criterion and the Cohesive Zone Model (CZM) with bilinear traction-separation law was performed using the MAT-54 (ENHANCED_COMPOSITE_DAMAGE) material model. Among the five different cores, Trapezoidal core has the highest peak force average of 2.9 kN while Triangular core sandwich structure has the lowest with 1.23 kN. Absorbed energy efficiency average was highest for rectangular core with 0.95 and lowest for sinusoidal core with 0.69. The specific absorbed energy value was highest for Triangular core with 0.312 J/g and lowest for Sinusoidal core with 0.178 J/g. The damage area on the structure increased with increasing curve angle. It was determined that the core structure and curve angle is an effective parameter on peak force and energy absorption efficiency.
Keywords: cohesive zone model (CZM); curved sandwich composite; finite element method; low velocity impact test; progressive damage analysis